Implementation of Mind Mapping as a Teaching Medium to Improve Reading Comprehension in Grade VII at SMP Negeri 2 Jalaksana - Tuzahra, Siti Nur AlFiah; Ropiah, Opah (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
This study aims to determine the effect of using mind mapping learning media on students' learning outcomes in reading fairy tales in Sundanese language lessons in grade VII at SMP Negeri 2 Jalaksana. The problems encountered in teaching fairy tale reading are low student interest and understanding of the reading content, as well as the dominance of conventional methods used by teachers. This study employs a quantitative approach using an experimental method and a One Group Pretest-Posttest design. The research sample consists of students from class VII-A selected through simple random sampling. The instruments used include pretest and posttest assessments to measure improvements in learning outcomes. The results of data analysis using a paired sample t-test showed a significant difference between pretest and posttest scores with a significance value of 0.000 (p < 0.05). This proves that the use of mind mapping has a positive and significant effect on students' fairy tale reading skills. This medium helps students understand the elements of fairy tales visually and systematically, as well as increasing active involvement in the learning process.